The Role of Mediating Islamic Personality and Value Satisfaction on the Effect of Relationship Marketing on Customer Loyalty - Bambang Widarno (Journal of Digital Marketing and Halal Industry, 2020)
The study of consumer loyalty to a product is an essential topic for academics and practice. There is not much empirical research on the effect of marketing on allegiance, based on the literature review; it has produced propositions that determine consumer loyalty in a product that is influenced by marketing effectiveness. This study uses a qualitative approach to using literature studies. Based on a literature review, it produces propositions that determine consumer loyalty in a product that is influenced by marketing effectiveness. Besides, there is a mediating effect of Islamic personality and consumer perceived value satisfaction. This study also links value satisfaction and customer value loyalty. Islamic personality is a mediating variable. This study also discusses the combination of perceived value and consumer satisfaction into value satisfaction.